Hubungan Persepsi Mahasiswa Tentang Laboratorium Terpadu Perbankan Syariah Terhadap Pencapaian Pembelajaran - Lemiyana Lemiyana; Tariza Putri Ramayanti (JAS-PT (Jurnal Analisis Sistem Pendidikan Tinggi Indonesia), 2022)
This study aims to determine the relationship between student perceptions of the integrated laboratory on learning achievement. The research method is a quantitative method, the sample of this research consists of 233 students who have used an integrated laboratory in the Islamic Banking study program using purposive sampling and using SPSS as an analytical tool. The results of this study indicate that there is a positive and significant relationship between students' perceptions of the integrated laboratory on learning achievement.